An English Twig and an Irish Shillelee!! - (:unkn) unknown (Holland, William, 1800)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Cotter, Patrick, 1759 or 60-1806